A validated NMR approach for MDMA quantification in Ecstasy tablets - Almeida, Nathalia S. (2018)
In recent years, ecstasy trafficking has grown in complexity and tablets has been commonly sold containing different contents of 3,4-methylenedioxymethamphetamine (MDMA) or even other psychoactive substances. In contrast, identification and quantification of drugs of abuse is still a challenge, once the access to drug standards is very restricted in Brazil. In this work, ecstasy tablets seized by the Brazilian Federal Police have their chemical composition identified and quantified by gas chromatography and quantitative 1H nuclear magnetic resonance based on an internal standard approach (IS-1H-qNMR). Both methods were validated and showed suitable results for the figures of merit. IS-1H-qNMR shows excellent results of accuracy (relative error < 5%) and precision (relative standard deviation (RSD) < 2%). Comparatively, IS-1H-qNMR is more efficient and versatile than gas chromatography to accomplish in a single analysis the identification and quantification of target analytes. Since the method does not require a specific reference material, it is cost effective and provides agility to routine forensic analysis.